Pengaruh Green Marketing dan Sosial Media Terhadap Repurchase Intention Brand Image Sebagai mediasi Fore Coffee di Denpasar - Angelina Made Elva Dwi Jayanthi; Ni Wayan Lasmi (Jurnal Manajemen dan Ekonomi Kreatif, 2026)
This study aims to determine the effect of green marketing and social media on brand image and repurchase intention, as well as the mediating role of brand image on the influence of green marketing and social media on repurchase intention. The location of this study was Fore Coffee in Denpasar and the sample used was 150 respondents. Data analysis techniques were carried out using SmartPLS 4. The results showed that green marketing had a positive and significant effect on repurchase intention, social media had a positive and significant effect on repurchase intention, green marketing had a positive and significant effect on brand image, social media had a positive and significant effect on brand image, brand image had a positive and significant effect on repurchase intention, brand image was proven to be able to provide a positive and significant mediating effect on the relationship between green marketing and brand image and brand image was proven to be able to provide a positive and significant mediating effect on the relationship between social media and repurchase intention. Suggestions that can be given by researchers are. The recommendations in this study are that Fore Coffee management should provide compelling information about environmental friendliness on product packaging, provide more frequent information about environmental friendliness directly to consumers when shopping or through social media, consistently provide honest and up-to-date information to consumers, expand international branches to increase their popularity, continue to innovate their products, and improve their service quality.